A FUNDAMENTAL PRECAMBRIAN-PHANEROZOIC SHIFT IN EARTH'S GLACIAL STYLE? - Evans D.A.D. (My University, 2003)
It has recently been found that Neoproterozoic glaciogenic sediments were deposited mainly at low paleolatitudes, in marked qualitative contrast to their Pleistocene counterparts. Several competing models vie for explanation of this unusual paleoclimatic record, most notably the high-obliquity hypothesis and varying degrees of the snowball Earth scenario. The present study quantitatively compiles the global distributions of Miocene–Pleistocene glaciogenic deposits and paleomagnetically derived paleolatitudes for Late Devonian–Permian, Ordovician–Silurian, Neoproterozoic, and Paleoproterozoic glaciogenic rocks. Whereas high depositional latitudes dominate all Phanerozoic ice ages, exclusively low paleolatitudes characterize both of the major Precambrian glacial epochs. Transition between these modes occurred within a 100-My interval, precisely coeval with the Neoproterozoic–Cambrian “explosion” of metazoan diversity. Glaciation is much more common since 750 Ma than in the preceding sedimentary record, an observation that cannot be ascribed merely to preservation. These patterns suggest an overall cooling of Earth's longterm climate, superimposed by developing regulatory feedbacks involving an increasingly complex biosphere.
Keywords: Glaciation; Phanerozoic; Precambrian; Paleozoic; Tectonics; Paleoclimate; Climate feedbacks; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская